PERILAKU KESELAMATAN DAN KESEHATAN KERJA DALAM PENGGUNAAN APD PADA PETANI PENGGUNA PESTISIDA DI SERDANG BEDAGAI - Amelia Fernanda; Susilawati (Jurnal Kesehatan, 2024)
Farmers are a job that is very at risk of experiencing poisoning due to pesticides, many of which are the factors that cause poisoning, such as environmental factors and the behavior factors of the farmers themselves every time they use or have direct contact with pesticides. Pesticide poisoning can be minimized by improving behavior when using pesticides and using complete PPE. This study aims to describe the behavior of farmers, by knowing the knowledge, attitudes and actions of farmers in Serdang Bedagai. The method in this research is descriptive, the sampling technique uses purposive sampling, with a total population of 75 people, the primary data is obtained by observing and interviewing using a questionnaire, and the data obtained will then be processed univariately for all variables in the study. The results showed that out of 31 respondents, 12 respondents (38.7%) had good knowledge of farmers, 18 respondents (58.1%) had attitudes in the sufficient category, 28 respondents (90.3%) had actions in the poor category. Of the 31 farmers in Bonto Village, they already had fairly good knowledge and attitudes, but the opposite was true with very little action. It is hoped that the farmers in Bonto Village will remind each other about the use of PPE, and it is hoped that farmer groups or related agencies and the agricultural service will supervise farmers so that they have awareness of using PPE.